1879. A Point Prevalence Study of Antibiotic Utilization in 61 Geographically Diverse Acute Care Hospitals (2017). (26th November 2018) - Kuper, Kristi; Kinn, Patrick; Postelnick, Michael; Gibson, Amanda; Pakyz, Amy; Schulz, Lucas T
Abstract: Background: Antibiotic utilization for geographically diverse areas can be difficult to obtain. The purpose of this study was to characterize patterns of US antibiotic use over a defined period to provide comparative data for benchmarking and to assist with identifying antibiotic stewardship opportunities. Methods: Data were obtained as part of a larger study evaluating antibiotic time out practices. Participating institutions submitted de-identified patient-level antibiotic use data from a single day (between October 16, 2017 and November 17, 2017). Indication, expected duration, and antibiotic stop dates were documented. Antibiotics were classified by American Hospital Formulary Service (AHFS) therapeutic category and evaluated to identify duplicate anti-anaerobic, anti-MRSA, and AHFS classes. Hospital teaching status and US Census region were recorded. Results: A total of 6, 184 courses of therapy (8, 996 individual antibiotics) were evaluated from 61 hospitals. Sixty-four percent of therapy courses submitted were from academic medical centers. Distribution by census region was Midwest (44.7%), Northeast (15.11%), South (23.2%), and West (16.9%). Over half (53.7%) of therapy was empiric and 33.4% was directed. Sixty-six percent of courses did not include a stop date within the electronic medical record. Twelve drugs comprised 80% of total antibiotic use. Percentage of antipseudomonal use was similar across regions, but anti-MRSA therapy was higher in the South and Midwest. Duplicate β-lactam therapy and duplicate anti-anaerobe therapy were identified in 1.5% of total courses (each). Duplicate anti-MRSA therapy occurred in 0.29% of therapy courses. Three percent of patients developed a Clostridium difficile infection during their hospitalization. Conclusion: Vancomycin and piperacillin–tazobactam were the most common antibiotics used which is consistent with other analyses, but anti-anaerobic use as a percentage of overall use was higher than expected. Duplicate anti-anaerobe and β-lactam therapy is less frequent, but still represents an opportunity for stewardship. Antipseudomonal and anti-MRSA agents represent two key categories for stewardship given the high percentage of use. The addition of a stop date to the antibiotic order presents an opportunity to improve overall utilization. Disclosures: All authors: No reported disclosures.